The Relationship Between Peer Conformity and Permissive Parenting in the Case of Discipline Behavior at Class XI and XII Private High School Students in Sidoarjo - Dewi Nur A’isyah; Lely Ika Mariyati (Proceedings of The ICECRS, 2020)
The purpose of this study was to determine the relationship of peer conformity and permissive parenting with the discipline behavior of class XI and XII students at Sidoarjo High School. This research is a quantitative correlational study using multiple regression methods. The research subjects used 222 students consisting of grade XI and XII Natural Sciences and Social Sciences students. Determination of research subjects using quota sampling techniques. The method of data collection uses a psychological scale, namely the Likert scale. The results of the study indicate that there is a negative relationship between peer conformity and permissive parenting with the discipline behavior of class XI and XII students at Sidoarjo High School. With a significance value of 0,000 <0.05 with a correlation coefficient of 0, 285 and a coefficient of determination of 7.3%. But this research cannot provide a large contribution. The implications for this study for students are expected to be more selective in choosing friends, while for parents it is expected to be more selective with whom children make friends, for the school can choose activities that are good for students and give parenting to parents about parenting.